INTERNALISASI NILAI-NILAI KEARIFAN LOKAL PADA PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Muflihin, Ahmad (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2020)
Indonesia is one of the largest multi-cultural countries in the world. This can be seen from how wide and diversity of socio-cultural and geographical conditions. Diversity is wealth for a nation. However, it can also be a source of conflict that is not properly managed. As a religion with 87.2% or 207 million Muslims in Indonesia, Islam has a very important role in maintaining this diversity, and this must be taught in education, especially in the subject of Islam. This research uses a descriptive qualitative approach. The type of research is library research. This article will be used to develop a curriculum, based on the values of cultural wisdom as an effort to care for diversity.Keywords: Local Wisdom, Curriculum Development, Islamic Education